HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENGGUNAAN ANTIBIOTIKA PADA MASYARAKAT NAGARI SIANOK ANAM SUKU - Widyastuti Widyastuti; Hafizah Hafizah; Hansen Nasif (LLDIKTI Wilayah X, 2021)
The use of antibiotics has now become a global health problem, mainly due to inappropriate use of antibiotics that can cause resistance. Knowledge and behavior are factors in the use of antibiotics. This study aims to look at the relationship of knowledge with behavior antibiotic use in the Nagari Sianok Anam Suku community. The study was conducted with a cross-sectional study using questionnaire of 96 respondents. Data were analyzed using Rank-Spearman correlation test. The results showed 54.2% of respondents had good knowledge and 51% of respondents had good behavior. The correlation between knowledge and behavior is very weak and unidirectional (r = 0.186), there is no significant relationship between knowledge and behavior (p = 0.069). Conclusion: There is no significant relationship between respondents' knowledge and behavior regarding the use of antibiotics